Analysis of a standby redundant system with controlled arrival of failed machines. (2018) - Chang, Fu-Min; Lee, Yu-Tang; Chang, Chia-Jung; Yeh, Chung
This paper deals with a queueing characterisation of a machine repair system with controlled arrival of failed machines. The maintenance facility will allow the failed machines to enter the system till full capacity, then no further arriving failed machines are allowed to enter the maintenance facility until the number of failed machines in the maintenance facility decreases to a certain threshold value. For such system, we derive the explicit expressions for the steady-state availability, the steady-state busy period, and the mean time to system failure. We also perform a parametric analysis for investigating the effect of changes in the system parameters on the total expected profit function. Several cases are analysed graphically to study the effect of various parameters on the reliability and mean time to failure (MTTF) of the system.